In partial fulfillment of the requirements for Bachelor degree in Energy and Environmental Engineering - Thouqan, Eman; Ruzzeh, Zaina (My University, 2021)
This project proposes two methods of electrification for a rural area which is Masafer Yatta, south of Hebron using an off-grid hybrid system based mainly on renewable energy sources (PV, wind turbine) and diesel generators, to electrify the regions in which the occupation prevents electricity access to it, which considered as Area C, the project is located in two locations in Masafer. The average energy demand in the first site which contains 72 families is 2075 kWh/day. for the second site which contains 30 families, the average energy demand is 1015 kWh/day. The region has good renewable energy potentials, where the average solar radiation there is 5.15 kWh/m2.day and the average wind speed in Masafer Yatta at the first site is 4 m/s and the second site is 5.4 m/s. HOMER software was used to optimize the design of renewable energy in remote areas which requires solar radiation data, wind speed data, electrical demand profile for the two locations proposed. The results showed that the best option for the electrification of Masafer Yatta after studying the region from a political and social point of view is wind turbines with a capacity of 920 for 72 kW families and 300 kW for 30 families with the first diesel generator capacity of 240 kW and 120 kW for the second site. In the end, the effect of wind turbines on the environment was studied. Finally, it was found in this project that electrifying remote areas that are far from the electric grid using a hybrid wind power system with diesel generators is the most appropriate solution, especially if these areas suffer from political and social problems, as is the case of Masafer Yatta, it was also found that it was environmentally friendly and clean, which confirmed that the choice of wind energy was the best and suited for this area.